Deciphering CD137 (4‐1BB) signaling in T‐cell costimulation for translation into successful cancer immunotherapy. Issue 3 (9th February 2016) - Sanchez‐Paulete, Alfonso R.; Labiano, Sara; Rodriguez‐Ruiz, Maria E.; Azpilikueta, Arantza; Etxeberria, Iñaki; Bolaños, Elixabet; Lang, Valérie; Rodriguez, Manuel; Aznar, M. Angela; Jure‐Kunkel, Maria; Melero, Ignacio
Abstract : Interplay of CD137 signaling and cancer immunotherapy by means of costimulating T and NK cells. The scheme highlights the potentiation of antitumor antibody‐dependent cell‐mediated cytotoxicity and adoptive T‐cell therapy by anti‐CD137 mAbs. Abstract : CD137 (4‐1BB, TNF‐receptor superfamily 9) is a surface glycoprotein of the TNFR family which can be induced on a variety of leukocyte subsets. On T and NK cells, CD137 is expressed following activation and, if ligated by its natural ligand (CD137L), conveys polyubiquitination‐mediated signals via TNF receptor associated factor 2 that inhibit apoptosis, while enhancing proliferation and effector functions. CD137 thus behaves as a bona fide inducible costimulatory molecule. These functional properties of CD137 can be exploited in cancer immunotherapy by systemic administration of agonist monoclonal antibodies, which increase anticancer CTLs and enhance NK‐cell‐mediated antibody‐dependent cell‐mediated cytotoxicity. Reportedly, anti‐CD137 mAb and adoptive T‐cell therapy strongly synergize, since (i) CD137 expression can be used to select the T cells endowed with the best activities against the tumor, (ii) costimulation of the lymphocyte cultures to be used in adoptive T‐cell therapy can be done with CD137 agonist antibodies or CD137L, and (iii) synergistic effects upon coadministration of T cells and antibodies are readily observed in mouse models. Furthermore, the signaling cytoplasmic tail of CD137 is a key component of anti‐CD19 chimeric antigen receptors that are used to redirect T cells against leukemia and lymphoma in the clinic. Ongoing phase II clinical trials with agonist antibodies and the presence of CD137 sequence in these successful chimeric antigen receptors highlight the importance of CD137 in oncoimmunology.